As Cartas De Guy de Maupassant - Hervot, Brigitte Monique [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
Esse trabalho tem como objetivo tecer algumas considerações acerca de uma crônica de Guy de Maupassant (1850-1893), intitulada Le style épistolaire. Publicado no jornal Le Gaulois, no dia 11 de junho de 1888, o texto aborda alguns aspectos importantes do gênero em questão, entre outros, o missivista, tanto o remetente quanto o destinatário, ou ainda, o teor e o estilo das cartas. Revela como Maupassant concebia a arte de escrever cartas, e entender sua visão é um passo importante para adentrar a produção epistolar do próprio autor que, entre 1862 e 1891, escreveu mais de 750 cartas.

The proposal of this paper is to points out some considerations concerning a Guy de Maupassant‘s (1850-1893) chronicle entitled Le style épistolaire. It was published in Le Gaulois journal on June 11th 1888, and it approaches some important aspects on its gender, such as the missive, that is, the sender and/or the addressee; and more, the content and the style of the letters. It also discloses how Maupassant conceived the art of writing letters. Understanding his viewpoints is a crucial step to permeate his epistolary production that, between 1862 and 1891, wrote more than 750 letters.
The letters of Guy de Maupassant
Keywords: Guy de Maupassant; French literature; correspondence; Guy de Maupassant; literatura francesa; correspondência